APPLICATION OF IMAGE CONTINUITY IN DOKUMENTARY PROGRAM EDITING “ RAGAM RASAM-MAN OF UMBI” - Marwiyati Marwiyati; Noufal Agis Alfikri Ramadhani (Sean Institute, 2023)
Interception between picture visualization and consistency or continuity in an audio visual works happens often. Such as the discontinuity between the images and the narration, the discontinuity between the intersection of the images and the rhythm of the music, and no color discontinuity between the images. The objective from producing this production work is for creating the images or pictures continuity through technical methods, which include cutting by narration, cutting by rhythm, color correction, and color grading therefore to analyze the objectives in this final documentary program work titled “Ragam Rasam – Man of Umbi”. Based on the result from this final work, the implementation of cutting by narration and cutting by rhythm can produce a documentary program that is harmonious and comfortable to watch. Cutting by narration produces the cut, and the images’ choices can match the narrative conveyed. Therefore, the information can be easily delivered to the viewers. The cutting by rhythm technique resulting in the cutting of the images changes every music tempo, this technique produces the images sequence being easier to understand by the viewers. Afterwards, from the implementation of color correction, could produce images with balanced light and color along with color standardization to perform color grading. From the implementation of color grading, the writer can produce images that match with entire images and story. The color grading technique also corrects the colors that appear out of alignment to be a color that matches the other colors in the images.